Finite element modeling of heat transfer in salt bath furnaces (2009)
"Heat flow patterns in two salt bath furnaces were studied in this work using finite element(FE) analysis. The implications of the heat flows on long term stability of furnace performance were evaluated. One design had a purely silica brick back-up after the embedded heating element with asbestos and glass-wool fiber insulation just before the outer steel shell. The other had an additional air-gap insulation formed by cylindrical steel belts with spacers placed after the silica back-up. It was observed that the design with additional air-gap insulation had tremendous insulation effect, necessitating a drastic thinning down of the silica brick thickness and glass wool fiber. "